Determination of heavy metal pollution in depth profile of marine sediment samples from the Strait of Malacca - Elias, Bin Saion; Ab Khalik, H. Wood; Zainal Abidin, Sulaiman; Awad A., Alzahrany; Md Suhaimi, Elias; Wee, Boon Siong (PSP, 2007)
In this study, four core marine sediment samples from the Strait of Malacca were collected and analyzed by using instrumental neutron activation analysis (INAA). This work was carried out to evaluate the level of heavy metal pollution in the water-body. In addition, inductively coupled plasma-mass spectroscopy (ICP-MS) technique was used for non-measurable elements by INAA. The following heavy metals (As, Cd, Cr, Cu, Fe, Mn, Ni, Pb, Sb and Zn) have been determined in the core sediment samples collected from the Strait of Malacca. Moreover, the obtained results were compared to the national studies and the international guidelines for marine sediments.